Penggunaan Metode Ward and Peppard dalam Perencanaan Startegis Sistem Informasi: Systematic Literatur Riview - Muhamad Rizky (Universitas Katolik Widya Karya Malang, 2024)
The Strategic planning of information systems needs to be used, because it can support business strategies in organizations/companies in order to achieve business goals more quickly. One method that can be used in strategic planning of information systems is the Ward and Peppard method. This method has a clear framework and also has analytical techniques that focus on business needs & information technology for the future. The purpose of this study was to see the use of the Ward and Peppard method in strategic planning of information systems. The method used in this research is literature study. The results of this study are the Ward and Peppard method in strategic planning of information systems can be used as a method of choice that can be used in strategic planning of information systems in various sectors of life.